-8-2t=-t

Simple and best practice solution for -8-2t=-t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8-2t=-t equation:



-8-2t=-t
We move all terms to the left:
-8-2t-(-t)=0
We add all the numbers together, and all the variables
-2t-(-1t)-8=0
We get rid of parentheses
-2t+1t-8=0
We add all the numbers together, and all the variables
-1t-8=0
We move all terms containing t to the left, all other terms to the right
-t=8
t=8/-1
t=-8

See similar equations:

| 63=8y | | -4u+2=-32 | | 0=4x-64x+192 | | -3/4x+3=15 | | 8.7+w=5.7 | | 4|u+2|=-32 | | 70+35+4x+12=180 | | (5-t)+(3t+2)=t | | -65t+15=-9.7+43.8 | | y4–3y2+1=0 | | X+x+122=180 | | p+(-26=-13.8 | | 2t-27=0 | | 10×-23=29-3x | | (5-1)+(3t+2)=t | | 4n+n+1=50 | | 480(1+0.9)^n=1042.51 | | x/2-6=-15 | | 480(1+0.9)^n=1042.521 | | -1x-8=-23 | | 64=54+r | | -6=2(w+5)-4 | | 3/4(4/5x-2)=-1 | | 1042.51=480(1+0.9)^x | | 2x-3+8=26 | | 9^2x-1=6^x | | 5(x=9)-4=51 | | −2(7−4x)=1/2(4+16x)−16 | | 2(3x-9)=5x+5 | | -5.9-8.8x=-19.1 | | 7x+4=3(5x-4) | | 2b^2+3=-5b |

Equations solver categories